The Effect Of Infant Massage On Infant Sleep Quality - Lumastari Ajeng Wijayanti; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Good sleep quality is essential for infant growth and development. Adequate sleep supports neurological maturation, physical growth, and cognitive development. Infant massage is a widely used non- pharmacologically intervention that provides relaxation and improves sleep quality. Objective: To determine the effect of infant massage on infant sleep quality. Methods: This quantitative study employed a pre-experimental one group pretest-posttest design. Thirty infants aged 1–6 months were selected using purposive sampling. Infant massage was performed for four weeks. Sleep quality was assessed before and after the intervention using an observation checklist and infant sleep diary. Data were analyzed using descriptive statistics, the Shapiro – Wilk normality test, and the Paired Sample t- Test . Results : The mean sleep quality score increased from 6.45 ± 1.18 before the intervention to 8.63 ± 0.97 afterward . The Paired Sample t- Test showed a statistically significant improvement ( p = 0.001 ). Conclusion : Infant massage effectively improves infant sleep quality and can be used as a complementary intervention to optimal infant support development . Keywords : infant massage , sleep quality , infant , tactile stimulation , growth and development .